Immortalized - Disturbed (Musical group) (Burbank, CA Reprise Records, 2015)
After a four-year hiatus, hard rock titans Disturbed announce their return with their sixth studio album, which features the lead single The Vengeful One. Their last album, Asylum, was the band's fourth consecutive number one release.
The eye of the storm -- Immortalized -- The vengeful one -- Open your eyes -- The light -- What are you waiting for -- You're mine -- Who -- Save our last goodbye -- Fire it up -- The sound of silence -- Never wrong -- Who taught you how to hate.
Title from disc label.
Lyrics and full credits on container insert.
Lyrics and full credits on container insert.
Performed by Disturbed (David Draiman, vocals ; Dan Donegan, vocals ; guitars, ebow, keyboards, bass ; Mike Wengren, vocals, drums, percussion) ; with additional musicians.
"Parental advisory: explicit content"--Container insert.
104482
Keywords: 2011 - 2020; Heavy metal (Music); Rock music -- 2011-2020.; Alternative metal (Music); Rock music; Heavy metal (Music); Alternative metal (Music)